Easy Japanese : a Direct Learning Approach for Immediate Communication (Japanese Phrasebook). - Samuel (Tuttle Publishing, 2013)
This is a carefully structured, practical book for learning colloquial spoken Japanese. Each lesson presents a few of the most common features of the language in sentences which are short, easy, and immediately useful. The first thirteen lessons show you there is a lot that can be said with just a word or two. The later lessons introduce more variety and explain a few of the fine points. The sentences reflect how the Japanese language is really spoken. They are short but colloquial, abrupt but not rude. Each lesson contains first a number a number of Japanese phrases followed by material f.